Enhancement the feeding value of rice straw as animal fodder through microbial inoculants and physical treatments - Mona S. Zayed (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose Improving the nutritional value of rice straw by microbial inoculants and some physical treatments for animal feeding during dry seasons. Methods Different microbial inoculants and some physical treatments were used to improve the nutritional value of rice straw. Rice straw was divided into moist straw, soaked straw for 24 h without pasteurization and soaked for 24 h and pasteurized at 100 °C/1 h, and all of them were inoculated with different microbial inoculants. Results Moistened rice straw inoculated with Azotobacter chroococcum and Saccharomyces cerevisiae recorded the highest significant reduction in organic matter percent, 74.21%. The highest significant reductions in crude fiber, neutral detergent fiber, and acid detergent fiber percent were recorded in moistened rice straw inoculated with Azospirillum brasilense and Saccharomyces cerevisiae which gave 27.54, 55.39 and 42.47%, respectively. The highest significant increase in crude protein percent, 13.71%, was recorded in rice straw soaked for 24 h and inoculated with Azospirillum brasilense and Bacillus megaterium. The combined interaction between microbial treatments and physical pretreatments of rice straw gave a significant decrease in organic matter, crude fiber, neutral detergent fiber and acid detergent fiber %, as well as a significant increase in crude protein % compared to control. Addition of nitrogen fixers to rice straw improved its nitrogen contents. Conclusions This study showed the possibility of improving the nutritional value of rice straw using microbial inoculants and some physical treatments to produce safe and cheap animal feeds.